Promin / Airina Fitri Rosaffedy and Norarifah Ali - Rosaffedy, Airina Fitri; Ali, Norarifah (Faculty of Art and Design, 2021)
The world’s most focused issue today is related to a pandemic namely Covid 19. Malaysia is also among the countries affected by this pandemic and the government is trying to counter it from spreading. This situation has caused many activities such as social, business, leisure and education to be monitored and tightened in accordance with the instructions from the Ministry of Health Malaysia (KKM). Public transport operations are among the worst affected in the early stages of this pandemic issue. Public transport plays an important role in the society. It solves various problems such as traffic congestion, increased travel time, road accidents and environmental pollution. Due to the dependence of the community on private vehicles, public consumption of public transport in the country is still at a low level. Society is more geared towards consumers using privacy that promises comfort, speed and privacy. This has worsened in the transmission of COVID-19 since the beginning of this year. The use of public methods declined at a very significant rate, during the Movement Control Order (PKP) in many countries including Malaysia. It is also due to the new norms in today’s society with the culture of work from home and online learning. By using this product, we can maintain the distance between one user to another while on a bus. This product uses the sliding concept and this product is also shaped like a fan that makes it easy to store and can be opened easily for use.